Exploring Teachers' Professional Growth Through Reflective Practice in School Settings - Kaunickienė, Natalija; Bubnys, Remigijus (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
Teacher professional growth is a reflective and contextual process shaped by both personal and institutional factors. This study aim investigates how reflective practice within school settings fosters professional development, focusing on teachers’ experiences in a Lithuanian general education school implementing a unique personal professional development (PPD) framework. Sixteen teachers participated in semi-structured phenomenographic interviews to explore their reflective experiences. Analysis using phenomenographic methodology revealed three interrelated categories of professional growth: (A) changes driven by individual reflection, (B) collegial collaboration aligning personal and institutional goals, and (C) development enabled by the school’s organisational framework. These categories form a recursive structure within the PPD framework, where each one supports and enhances the others. This study emphasises Category A – reflection-driven growth – as a foundational method for learning from one’s own and others’ experiences. Teachers who engaged in continuous, systematic reflection – linking theory and practice – demonstrated improved self-awareness, enhanced pedagogical practice, and a stronger professional identity. Key elements contributing to growth include personal attitudes, student-focused teaching, and emotional engagement in teacher-student interactions. The findings highlight the significance of structured reflective practice as a catalyst for sustained teacher development in school contexts.